Negative Index Photonic Crystals Superlattices and Zero Phase Delay Lines" - Kocaman, S.; Wong, C. W.; Aras, M. S.; Hsieh, P.; McMillan, J. F.; Biris, C. G.; Panoiu, N. C.; Yu, M. B.; Kwong, D. L.; Stein, A. (IntechOpen, 2012)
None